(untitled) (Journal of Economic Research & Business Administration, 2021)
The article analyzes the system of state planning in Kazakhstan. The analysis and evaluation of the achievement of goals and target indicators in the strategic documents of the central state and local executive bodies is carried out. The analysis is based on studies of international organizations, reports of state bodies on strategic plans and programs for the development of territories, analytical reports of the Center for Research, Analysis and Evaluation of the Effectiveness of the Accounts Committee of the Republic of Kazakhstan. The standards and best practices of the Organization for Economic Cooperation and Development (hereinafter – the OECD) used by the governments of developed countries in the development of strategic documents and standards were considered. The main problem areas for the development of strategic documents by the state bodies of the country are indicated. The article concludes that the quality of strategic planning documents largely depends on the quality of predictive and analytical work and on the methodological tools that are available to government agencies. The authors also come to the conclusion that strategic documents should be focused on solving current problems of society, they should clearly observe the principle of decomposition of goals, and when developing them, alternative solutions to the problems that these documents are aimed at should be considered in order to ensure the choice of the best and most effective solutions available to society. Key words: strategic planning, strategic goals, target indicators, analysis, evaluation, government agencies.